MANAJEMEN KURIKULUM BERBASIS PROGRAM DI SMP ISLAM BANI HASYIM - Qurroti A'yun (VICRATINA, 2018)
The program curriculum designed and compiled at the Bani Hasyim Islamic MiddleSchool is a curriculum that was developed by integrating and based on the school'svision and mission. In this study using descriptive qualitative. The programcurriculum model at Bani Hasyim is synergizing 19 programs in various subjects. The program activities are carried out by all Bani Hasyim Islamic Middle Schoolacademics namely students, teachers, and employees. Basic abilities equip students in ways of learning that are meaningful, resulting in a sense of independence,awareness, and movement. Learning activities carried out according to developmentand growth through exploration, discovery, heart, and emotional.Keywords: Curriculum, Program Based